Regulasi Diri Pada Karyawan Startup Yang Memiliki Turnover Intention - Rahmasari, Dewi Hajar; Abdullah , Sri Muliati (Green Publisher Indonesia, 2025)
This study aims to analyze self-regulation among startup employees who exhibit turnover intention. Turnover intention refers to an employee’s intention or tendency to leave a company, either voluntarily or due to termination factors. This research employs a qualitative approach with a case study method. Data were collected through semi-structured interviews with two female participants in their 20s who work at startup company X. The findings reveal that self-regulation plays a crucial role in decision-making related to the intention to leave, with family factors, social support, and career planning being key elements influencing such decisions. Additionally, the analysis shows that strong self-regulation helps employees set goals, plan for the future, and manage emotions when facing work-related stress. This study provides new insights into the relationship between self-regulation and turnover intention, particularly among young employees in the startup industry.